Effects of axitinib and lenvatinib on cardiovascular function and haemodynamic. (10th June 2022) - Pannucci, P; March, J; Cooper, SL; Hill, SJ; Woolard, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): EU Horizon 2020 Research and Innovation programme, under the Marie Skłodowska-Curie European Training Network Background: The introduction of novel anticancer treatments, targeting vascular endothelial growth factor receptors (VEGFRs), has changed the therapeutic approach in oncology. However, with their introduction in clinical practice, unanticipated cardiovascular complications emerged, including hypertension, left ventricular dysfunction and thromboembolism [1]. Even though these therapeutics strongly affect haemodynamic balance in patients, the pathophysiological mechanisms by which they impair cardiovascular function are still largely unknown, leading to a reduction of therapeutic dosage or to a temporary or permanent treatment interruption [2]. Purpose: The severity of cardiovascular complications following the treatment with VEGFR inhibitors, along with the lack of antihypertensive strategies able to adequately manage these events, require an unequivocal and urgent assessment of their cardiovascular safety. This study aims to determine the extent to which VEGFR inhibitors impact on cardiovascular function, profiling their effect on regional haemodynamic responses. Their cardiovascular assessment represents a valuable opportunity to investigate the mechanisms underlying cardiovascular toxicities induced by these novel antiangiogenic treatments. Methods: This study evaluated the haemodynamic effects of selected receptor tyrosine kinase inhibitors (RTKIs), namely axitinib and lenvatinib, in conscious and freely moving rats using the Doppler Flowmetry technique. Male Sprague Dawley Rats (350-450 g) were chronically implanted with pulsed Doppler flow probes (around the renal and mesenteric arteries, and the descending abdominal aorta) and catheters (jugular vein and distal abdominal aorta) [3]. Haemodynamic parameters were measured over 4 days, before and after daily administration of axitinib (3 and 6 mg/kg, 3 and 6 mg/kg/h for 1 h, i.v.), or lenvatinib (3 and 6 mg/kg, 3 and 6 mg/kg/h for 1 h, i.v.). Results: Both axitinib and lenvatinib evoked a significant hypertensive response, which progressively increased over the 4 days. This pressor effect was associated with a notable decrease of vascular conductance in the hindquarters. Lenvatinib caused a more marked vasoconstriction in mesenteric and renal vessels when compared to axitinib, which only elicited a renal vasoconstrictive effect at the highest dose used. Conclusions: This study showed that the axitinib- and lenvatinib-induced hypertensive response is associated with regionally selective vasoconstrictions, which consistently occur in the hindquarters vascular bed. However, their vasoconstrictive profile differs in the renal and mesenteric vasculature. In addition, the Doppler Flowmetry model showed to be a translational approach to predict the detrimental cardiovascular effects of these anticancer drugs, since the increase in blood pressure observed with this method reflects the hypertensive response reported in clinical practice.